Nepotism Practices in Recruitment Lead to Declining Performance of Educational Personnel: A Case Study at Bosowa University - Wirawan (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
This study seeks to examine the impact of kinship-based recruiting practices (nepotism) on the reduction in educational staff performance at Bosowa University, with an emphasis on mass recruitment in 2025, which is expected to include features of nepotism. An explanatory survey design is combined with a quantitative approach in the study methodology. The 107 educational staff members of Bosowa University in 2026 make up the study population, and a complete sampling technique is used. Questionnaires, interviews, observations, and personnel data recording were used to gather data. Descriptive statistics, basic linear regression, and various tests were employed in data analysis. Kinship-based recruitment procedures fall into the top category, according to the study's results (score 4.17). An estimated 52% of the 42 educational employees hired between 2023 and 2025 did so through non-competitive means that included nepotism. The performance of education staff hired prior to 2023 (score 3.70) and those hired between 2023 and 2025 (score 2.31) differs significantly, by 37.6%. 48.3% of the reduction in performance is positively and significantly impacted by family-based recruitment techniques. For education staff hired through non-merit methods, this report suggests implementing a meritocracy system, thorough HR audits, and competency improvement initiatives.